1977
DOI: 10.1007/bf01922292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on polyribosome structure and function in mouse liver

Abstract: Cadmium chloride injected to mice (20 micronmoles/kg) provokes in the livers a degradation of polyribosomes and diminishes their protein synthetic ability measured in vitro. CdCl2 added in a final concentrations between 30 and 100 micron to the protein synthetic cell-free system derived from livers of control mice inhibits its activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This method was advantageous, in that it requires small quantities of tissue (< 15 mg) and has high accuracy and sensitivity. Our results (Table 3) indicate that levels in excess of 8,000 ,ug/g were attained in play some degree of cytotoxicity (4)(5)(6)(7)(8)(16)(17)(18)(19)(20). Lung inflammation and necrosis are typically seen in response to aerosols containing 10 mg/m3, causing a disruption in mucociliary function.…”
Section: Resultsmentioning
confidence: 81%
“…This method was advantageous, in that it requires small quantities of tissue (< 15 mg) and has high accuracy and sensitivity. Our results (Table 3) indicate that levels in excess of 8,000 ,ug/g were attained in play some degree of cytotoxicity (4)(5)(6)(7)(8)(16)(17)(18)(19)(20). Lung inflammation and necrosis are typically seen in response to aerosols containing 10 mg/m3, causing a disruption in mucociliary function.…”
Section: Resultsmentioning
confidence: 81%
“…The possibility that the particulate fractions were contaminated by cytosol was eliminated because the Cd content per protein of these fractions did not change after extensive washing. Since several authors have reported morphological changes of subcellular organelles (10-12) and dysfunction of mitochondria or ribosomes (13,14), then any Cd located in the mitochondria and microsomes may be expected to be involved in the toxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that oxidative phosphorylation by isolated mitochondria (13) and protein synthesis by isolated ribosomes (14) were depressed in Cd-fed rats. This suggests that the Cd, as located in subcellular organelles, may be a primary location for the subsequent toxic effect in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…which retain full activity. Cadmium added to the protein synthetic cell-free system derived from control animals has a biphasic effect, in low concentration (10"s M) it slightly stimulates, and in higher concentrations (3 -1 0 X 10~5 M) it inhibits the incorporation of a radioactively labelled amino acid into proteins (Gamulin et al, 1977). In the livers of rats treated with cadmium for 2 -3 weeks the activity both of polyribosome and cytosol fractions is diminished (Norton and Kench, 1977).…”
Section: Introductionmentioning
confidence: 99%